2021
DOI: 10.1177/08258597211050740
|View full text |Cite
|
Sign up to set email alerts
|

“Resuscitate and Push”: End-of-Life Care Experiences of Healthcare Staff in the Emergency Department – A Hermeneutic Phenomenological Study

Abstract: Objective Care in the emergency department focuses significantly on delivering lifesaving/ life-sustaining clinical actions, often with limited attention to health-related suffering even at the end-of-life. How healthcare staff experience and navigate through the end-of-life phase remains minimally explored. Thus, this study aimed to uncover the lived experiences of emergency department staff at the end-of-life. Methods van Manen’s hermeneutic phenomenological approach was used. Nineteen healthcare staff were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…The mere fact they watch these children cry in pain stresses them so much. This study finding is consistent with 29 who identified Grief, sadness and helplessness as critical themes that emerged from a similar study.…”
Section: Discussionsupporting
confidence: 91%
“…The mere fact they watch these children cry in pain stresses them so much. This study finding is consistent with 29 who identified Grief, sadness and helplessness as critical themes that emerged from a similar study.…”
Section: Discussionsupporting
confidence: 91%
“…This is dissimilar to a previous study that assessed perspectives of promoting advance directives among nurses working in a hemodialysis room, in which more than 65% of those nurses were worried that discussing advance directives with patients might cause annoyance or discomfort [10]. A possible reason might be that as critical care nurses are frontline care providers who care for critically ill patients, they understand that advance directives would be one of the options to provide better end-of-life care and they have to face many patients with terminal illnesses and dying patients [19,20]. Also, we identified that compared to nurses who work in medical ICUs, those who work in cardiac and respiratory ICUs have lower motivation to promote advance directives.…”
Section: Discussionmentioning
confidence: 99%
“…Death is not welcomed in many societies 39 ; however, stroke patients' extensive struggles, avoidance over discussion of death, and communication difficulty at a late stage necessitate early action. Delineating the late stage survival situation and caregiving burden may outweigh some barriers of initiating PC early on, such as patients and family members' lack of awareness and professionals' reluctance to open difficult conversations 40,41 . Health professionals are in a unique position with expertise to initiate advance care planning to fully introduce PC 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Delineating the late stage survival situation and caregiving burden may outweigh some barriers of initiating PC early on, such as patients and family members' lack of awareness and professionals' reluctance to open difficult conversations. 40,41 Health professionals are in a unique position with expertise to initiate advance care planning to fully introduce PC. 40 To fill in the huge human resource gaps in PC service, professionals should be trained in a culturally and contextually appropriate approach to hone skills in physical care, communication, emotional support, and cognitive stimulation.…”
Section: Discussionmentioning
confidence: 99%